To Save the Truth: The Winding Road of the Positive Philosophy - Jankauskas, Skirmantas (Problemos, 1986)
An attempt is made to describe the development of the positive philosophy in the aspect of its conditionality by culturological presumptions. It is shown first how particular culturological presumptions have acquired shape in the attempts of G. Galileo to introduce the mathematical science of nature into the culture of Renaissance, and then how such presumptions have influenced the formation of positive philosophy by A. Comte and its further development by R. Avenarius, E. Mach, logical empirists, K. Popper, T. Kuhn, I. Lakatos and P. Feyerabend.